Normal Coordinate Analysis of Polyvinylidene Fluoride and Assignments of Raman and Infrared Bands - Prabakaran, A.R.; Mohan, S. (Asian Journal of Chemistry, 2010)
The laser Raman spectra of the two forms of polyvinylidene fluoride have been recorded on a Cary model 82 grating spectrophotometer. The infrared and far infrared spectra have also been recorded on Perkin-Elmer IR 781 and Polytech FIR 30 spectrophotometers respectively. The vibrational analysis has been carried out assuming C2v symmetry for form I and Cs symmetry for form II.